Arts of being Yorùbá : divination, allegory, tragedy, proverb, panegyric - Adéè̳kó̳, Adéléke (African expressive cultures., 2017)
There is a culturally significant way of being Yorùbá that is expressed through dress, greetings, and celebrations--no matter where in the world they take place. Adélékè Adék documents Yorùbá patterns of behavior and articulates a philosophy of how to be Yorùbá in this innovative study. As he focuses on historical writings, Ifá divination practices, the use of proverbs in contemporary speech, photography, gendered ideas of dressing well, and the formalities of ceremony and speech at celebratory occasions, Adéékó contends that being Yorùbá is indeed an art and Yorùbá-ness is a dynamic phenomenon that responds to cultural shifts as Yorùbá people inhabit an increasingly globalized world.